Hakikat kewujudan syarikat Islam sebagai sebuah entiti / Mohammad Zaid Daud@Daud Yatimee - Mohammad Zaid, Daud@Daud Yatimee (2009)
This Project Paper is written for the sake of deepen the knowledge of the author and others with regard to the unsolved issues those may be answerable by the contemporary Islamic Jurists whether the existence of an entity can be considered as a different entity from a human being. It has several characteristics which is quite similar in nature which belong to the human being and not the entity which differed from human being. The elaboration will be from the angle of definition, history, development, original nas, analogy and opinions from the contemporary Islamic Jurists. The author personally considers that this issue is the backbone of the banking issues nowadays. Just imagine that our contemporary Islamic Jurist argued limited only to the Islamic Banking Transaction despite the main issue of the existence of the Bank as separate legal entity itself has not been answered. This Project Paper will endeavor to study in great depth in order to satisfy the readers' even though the definite answer may be not find by the author. That is the beauty of Islam in fact. The need for ljtihad based on knowledge and not based on desire and satisfaction alone.